(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The tendency to identify leaking zones is essential tool in trap assessment. Faults play an important role in creation of hydrocarbon traps. For volumetric analysis of a field to be meaningful, it is essential to analyze the faults contributing to the accumulation of hydrocarbons in a trap. These faults may be sealing or act as conduit to fluid flow. Analysis of trap is therefore carried out with the aim to reduce the uncertainties associated with hydrocarbon exploration and exploitation in Niger-Delta using "Covenant” field as a case study. The aim of the study is achieved using three dimensional seismic and well log data. Three reservoirs were mapped on the field while the fault supporting the identified trap was analyzed via throw, shale volume, shale gouge ratio, and hydrocarbon column heights attributes. The volume of shale model shows the presence of shale and sandstone formations in the fault plane. The fault-horizon’s intersection (throw) model reveals that the horizons were not too deviated from where the maximum fault’s displacement was noticed. The estimated shale gouge ratio of the fault on the analyzed trap reveals that the shallow sand horizon is supported by moderate sealing plane while that of mid and deep sand horizons are supported by proper sealing fault plane. The hydrocarbon column height model reveals a column height of 120m supports the shallow sand horizon while column heights \(> 180\) m support the mid and deep sand horizons respectively. It was inferred that despite the three horizons are supported by sealing fault zone, leakage still occurs at shallow sand horizon which correspond to a moderately sealed plane from SGR.